PENENTUAN WAKTU ISTIRAHAT PEKERJA PEMBUATAN TEMPE âMUCHLARâ BERDASARKAN KRITERIA FISIOLOGIS - , AGRA ZULFANUDDIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tempe Murni Muchlar Industry is a home-based industry since 1985 and now engaged in the business of the making of tempe with traditional processing in the area of Kasihan, Bantul, Yogyakarta. The business owned by Mr. H. Muchlar and he has 10 employees, where the workers are doing activities of raw material sieving, washing, soaking, boiling, grinding, separation of the peel, cooling, fermentation, and packaging. The activities are done manually and it takes a long time, even the workers have to work in a standing posture which is can cause fatigue. The aim of the research is to determine the resting time also to determine the duration of resting time. Physiological criteria that being are observed heart rate, body temperature, and the level of sleepiness. Movement of the heart rate workers are observed, then the energy expenditure and duration of rest periods are calculated. Measurement of body temperature rhythm is observed in order to determine the body as well as to determine the break time. The level of sleepiness workers while working be obtained with Stanford Sleepiness Scale method. The result of research shows that based on physiological criteria, workers get off-time from working at 5 or exactly at 11:00 with the duration of rest periods on average 17 minutes. Keywords: heart rate, level of sleepiness , body temperature, time off